Psyllium fiber improves hangovers and inflammatory liver injury by inhibiting intestinal drinking - Yang, Keungmo; Ryu, Tom; Chung, Beom Sun (Frontiers in Pharmacology, 2024)
Excessive alcohol intake often results in hangovers and inflammatory liver damage, posing a significant health concern. Current treatment options for hangovers are still insufficient, highlighting the urgent need for new therapeutic approaches. Psyllium fiber (PF) is well-known for its gastrointestinal benefits, but its effect on hangovers is less explored. We utilized a mouse model with a single binge drinking (4 g/kg) to induce hangover and inflammatory liver injury. Intestine and liver injury were serologically and histologically estimated. Hangover symptoms were assessed using cylinder and footprint tests to objectively quantify hangover symptoms in mice. Binge drinking significantly activated alcohol-metabolizing enzymes in the small intestine and liver, leading to inflammatory damage. Concurrently, there was a rise in alcohol metabolites such as acetaldehyde and acetone, which exhibited a positive correlation with hangover symptoms in mice. Interestingly, the oral administration of PF (100 mg/kg) alongside alcohol consumption significantly reduced the activity of these enzymes and lowered the levels of alcohol metabolites. Mice treated with PF exhibited a considerable improvement in hangover symptoms and a reduction in hepatic inflammation, compared to control groups. Furthermore, in vitro experiments using HepG2 cell lines and semipermeable membranes demonstrated that PF effectively inhibits alcohol absorption into the body. In conclusion, PF demonstrates a potential protective effect against alcohol-induced hangover and liver injury by inhibiting the absorption of alcohol and lowering hangover-related alcohol metabolites. This study suggests that PF could serve as an effective therapeutic option for mitigating the adverse effects of excessive alcohol consumption.